2020
DOI: 10.1155/2020/6135149
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Increase of Snakebite Incidence in Relationship to Flooding Events

Abstract: Snakebite envenoming causes up to 138,000 deaths and 400,000 permanently disabled victims worldwide every year. Flooding is one of the many factors that seems to influence the incidence of snakebite. The catastrophic floods from late 2018 in Kerala (India) were widely broadcast and are an example of how flooding events are related to the increased incidence of snakebite. This relationship has been mentioned regularly in scientific and grey literature, but usually quite scarcely in comparison to other topics li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
1
14
0
1
Order By: Relevance
“…Recent studies have allowed to estimate human vulnerability to snakebite envenoming globally, by using proxy data on risk factors such as healthcare gaps, unavailability of antivenoms, and presence of medically important snake species [ 15 ], or through mathematical models [ 16 ], but without a direct measure of snakebite incidence and mortality. Additionally, new digital health applications have shown that it is partially possible to estimate areas of high snakebite incidence and identify populations at risk through citizen science [ 15 , 17 , 18 ] in countries where social media, citizen forums, and scientific online platforms are used to report snake-human encounters and map their geographic distributions [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have allowed to estimate human vulnerability to snakebite envenoming globally, by using proxy data on risk factors such as healthcare gaps, unavailability of antivenoms, and presence of medically important snake species [ 15 ], or through mathematical models [ 16 ], but without a direct measure of snakebite incidence and mortality. Additionally, new digital health applications have shown that it is partially possible to estimate areas of high snakebite incidence and identify populations at risk through citizen science [ 15 , 17 , 18 ] in countries where social media, citizen forums, and scientific online platforms are used to report snake-human encounters and map their geographic distributions [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, snakebite incidence also correlates with measures of presence, activity, abundance, or diversity of snakes ( Bravo-Vega et al, 2019 ; Goldstein et al, 2021 ; Hansson et al, 2013 ; León-Núñez et al, 2020 ; Schneider et al, 2021 ; Suraweera et al, 2020 ; Yañez-Arenas et al, 2014 , 2016 ) or with variables that affect snake activity. Often snakebite incidence increases during certain seasons when snakes and farmers are both more active such as in rainy or harvest seasons ( Chippaux, 2017 ; Ediriweera et al, 2018 ; Goldstein et al, 2021 ; Hansson et al, 2010 ; Mohapatra et al, 2011 ; Molesworth et al, 2003 ; Patiño-Barbosa et al, 2019 ; Suraweera et al, 2020 ), during flooding events ( Ochoa et al, 2020 ), or at higher temperatures, lower altitudes, and higher precipitation ( Angarita-Gerlein et al, 2017 ; Chaves et al, 2015 ; Chippaux, 2017 ; Ediriweera et al, 2018 ; Ediriweera et al, 2016 ; Goldstein et al, 2021 ; Hansson et al, 2013 ; Schneider et al, 2021 ; Suraweera et al, 2020 , Table 2 ).…”
Section: The Missing Link: How Do Humans and Snakes Interact To Create Spatio-temporal Patterns In Snakebite Incidencementioning
confidence: 99%
“…Such relationships with precipitation are likely driven by demographic and activity patterns of snakes in response to precipitation levels ( Chaves et al, 2015 ), and precipitation is also known to influence the composition of local venomous snake ensembles. Furthermore, flooding events are widely considered a primary driver of snakebite risk as they wash snakes towards lowlands which usually have higher population density ( Ochoa et al, 2020 ). On the other hand, the positive effect of temperature on snakebites may be related to overall diversity ( Luiselli et al, 2020 ).…”
Section: Eco-epidemiology Of Snakebitesmentioning
confidence: 99%
“…However, short term flooding events, such as monsoons, have been observed to lead to large numbers of snakebites by putting humans and snakes in proximity. The most likely mechanisms could be related to snakes being dragged by floodwaters from their natural home ranges or distributions (as has been the case of C. durissus in brazil; Bastos et al, 2005 ), to areas with higher human populations, and then seeking shelter from deep water in higher grounds along with people ( Ochoa et al, 2020 ). As climate change is altering the frequency, severity and location of flooding events, snakebite burden is expected to keep changing with flooding events.…”
Section: Eco-epidemiology Of Snakebitesmentioning
confidence: 99%
See 1 more Smart Citation